Enhanced Debye level in nano Zn1+xSb, FeSb2, and NiSb: Nuclear inelastic spectroscopy on121 Sb (Phys. Status Solidi B 5/2014). Issue 5 (May 2014) - Claudio, Tania; Bessas, Dimitrios; Birke, Christina S.; Kieslich, Gregor; Panthöfer, Martin; Sergueev, Ilya; Tremel, Wolfgang; Hermann, Raphael P.
<x xml:space="preserve">Abstract</x> By tuning a material's properties through nanostructuration, significant functional enhancements can be achieved. For thermoelectric materials, the figure of merit can be enhanced by proper nanostructuration, notably in reducing the thermal conductivity. The speed of sound – more precisely, the phonon group velocity – is an essential determining parameter for thermal conductivity. Measurements of the speed of sound in nanopowders were possible only through the use of nuclear inelastic spectroscopy, a technique which provides access to the element‐specific density of phonon states. This technique requires Mössbauer resonant nuclei in the sample, here antimony‐121, and a meV resolved synchrotron radiation beam, in this case provided by a sapphire backscattering monochromator installed at the ID18 nuclear resonance station of the European Synchrotron Radiation Facility. A direct comparison of the average speed of sound between three bulk and nano transition‐metal antimonides, respectively, reveals a significant increase in the Debye level, i.e. a decrease in the speed of sound in the nanophases. These results (see the Editor's Choice article on pp. 919–923) indicate that the reduction in the speed of sound is an important factor when discussing thermal transport in nanoparticle systems. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>